Evaluation of Self-transformational and Authenticity Among Students in College of Nursing - Idauli Simbolon; Mori Agustina br Perangin-angin (Fakultas Keperawatan, Universitas Klabat, 2020)
ABSTRACT Introduction: Authentic and Transformative leader are needed in nursing profession. This kind of leader is very important in creating healthy work environment in nursing practice. According to behavioral theory, leader can be made by learning some characteristics of previous successful leaders. Assuming this theory, authentic and transformative nursing leaders can be made. Therefore, nursing schools are responsible to produce such leader characters while they are in college. However, before employs certain strategies for the students it is better to evaluate their baseline authenticity and transformational traits first. So the aim of this study is to describe the authenticity and transformational characters of the freshman nursing students. The result will be benefit for nursing school to be used as a baseline in establishing certain strategies in the curriculum to maximize students’ authenticity and transformational characters to maximum level. Methods: The study using descriptive quantitative design with single point data collection by self-administered questionnaire that content 25 Authentic and Transformative behaviors. Sample of the study is freshman nursing students. Data is analyzed using SPPS with descriptive analysis. Results: The percentage of students who always practiced Authentic and Transformative characters is only 50,8 %. The highest percentage falls on character no.24 in which most of the students always use different stress management to reduce their stress (77,7%). Only five characters always performed 60%-77.7% and the rest 24 characters are below 60%. Conclusion: Most of the Authentic and &Transformational characters already practiced by freshman nursing students. However, the percentage of the students who practiced certain behaviors still low. It shows that there is still big room for improvement and developing those characters. KEYWORDS Authenticity; Evaluation; Transformational